The Encyclopedia of the Ghetto Lodz – an unfinished project of the archive from ghetto 1944 - Radziszewska, Krystyna (Acta Universitatis Lodziensis. Folia Germanica, 2017)
The article discusses “The Encyclopedia of the Ghetto”. Created in 1944 in the Łódź ghetto, it is the only text of this kind in the literature of the Holocaust. Its authors were inmates of the Łódź ghetto, hailing from both the city, as well as from the so-called “Old Reich”. They decided to describe the whole community along with its characteristic vocabulary in a form of an encyclopedia. Referring to the introduction by Oskar Rosenfeld dated December 1943, the article presents the idea behind the encyclopedia, its objectives, and its key assumptions. It discusses the structure and construction of entries. Examples have been provided of entries referring to various areas of the ghetto life, with certain entries notably missing from the text, the possible causes of which have been addressed in the article.